Model Pembelajaran Project Based Learning (PjBL) dalam Meningkatkan Kemampuan Berpikir Kritis Sekolah Dasar Guna Mendukung Pembelajaran Abad 21 - Selasmawati; Aprilia Tina Lidyasari (Postgraduate, University of Mataram, 2023)
This research aims to determine how the project-based learning (PjBL) learning model improves critical thinking skills in elementary schools. The research method used in this research is a literature study. Data collection techniques were done by reviewing articles from various national and international journal sources indexed by Google Scholar, Garuda, DOAJ, Springer, and others. Other sources are obtained with the help of Publish or Perish (POP) software. The research results show that the project-based learning model can improve students' critical thinking abilities. The project-based learning model is a project-based learning model where students are directly involved in the projects being created. Project-based learning emphasizes students being active because learning is student-centered and the teacher is a facilitator and motivator. Project-based learning answers the challenges of 21st-century learning. It should be developed and implemented in every subject and level of middle and high school education to improve aspects of 21st-century skills.